The Great Impersonation - Oppenheim, E. Phillips (Edward Phillips), 1866-1946 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Great Impersonation" by E. Phillips Oppenheim is a mystery novel published in 1920. When Englishman Everard Dominey encounters his German double, Leopold von Ragastein, in Africa, a dangerous plan unfolds to steal his identity and spy on English high society before World War I. Back in England, doubts emerge about the returned Dominey's true identity as he navigates a haunted estate, an unstable wife, political intrigue, and a mysterious ghost that may not be supernatural after all. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Great_Impersonation_(novel)
Release date is 2006-04-22
Produced by Dagny, John Bickers, and David Widger
Keywords: Spy stories